Strategi Pendidik dalam Mengoptimalkan Well-Being Anak Usia Dini di Lingkungan Sekolah - Dea Ayulia; Taopik Rahman; Risbon Sianturi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to explore teachers' strategies for improving children's psychological well-being in the school environment. The method used in this study is a literature review analyzing various child development concepts and relevant pedagogical strategies. The research findings indicate that children's well-being can be improved through four main strategies: strengthening emotional regulation, building secure attachment relationships between teachers and children, providing autonomy in learning activities, and creating an inclusive culture that fosters a sense of belonging in the classroom. Through these strategies, children feel more valued, secure, and have a higher motivation to learn. As a recommendation, teachers are expected to not only focus on academic achievement but also consistently build warm emotional interactions and create an inclusive physical and social environment. Furthermore, schools need to provide space for children's autonomy to develop independence and optimal mental health from an early age